Heterogeneous genetic cows of three genetic groups in feedlot system in the state of Pernambuco, Brazil - 10.4025/actascianimsci.v34i1.11306 - Christiano Raphael de Albuquerque Borges; Marcílio de Azevedo; Ivalda de Albuquerque Lima; Lúcia Helena de Albuquerque Brasil; Marcelo de Andrade Ferreira (Acta Scientiarum. Animal Sciences, 2011)
The behavior of 15 Girolando cows from three genetic groups (1/2, 5/8 and 3/4 HG) in feedlots was evaluated. Experimental design was completely randomized with 3 treatment (genetic groups) and 5 replicates. The animals were evaluated by the variables: food, rumination, rest, locomotion, water intake, demand and time in the shade, and other activities. Group 5/8 HG spent more time feeding (267.88 min.) than groups 3/4 HG (245.55 min.) and 1/2 HG (259.55 min.). Idle standing time was higher (204.66 min.) for 3/4 HG when compared to the other groups. There was no statistical difference for the duration of rest in the shade. Solar radiation and THI were the factors which most influenced the animals’ behavior. Results show that the genetic groups 5/8 and 3/4 HG had a higher sensitivity to heat than 1/2 HG